2016
DOI: 10.1111/epi.13359
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic electrographic changes after experimental traumatic brain injury

Abstract: Summary Objective To investigate possible electroencephalography (EEG) correlates of epileptogenesis after traumatic brain injury (TBI) using the fluid percussion model. Methods Experiments were conducted on adult 2- to 4-month-old male Sprague-Dawley rats. Two groups of animals were studied: (1) the TBI group with depth and screw electrodes implanted immediately after the fluid percussion injury (FPI) procedure, and (2) a naive age-matched control group with the same electrode implantation montage. Pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
89
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 40 publications
(66 reference statements)
13
89
0
1
Order By: Relevance
“…74 They found that a complex of repetitive HFOs superimposed on arcuate-shaped 10–16 Hz activity. These repetitive HFOs reflected population spikes with hypersynchronous multi-unit firing, and were only found in those FPI rats that later developed seizures.…”
Section: Hfos In Models Of Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…74 They found that a complex of repetitive HFOs superimposed on arcuate-shaped 10–16 Hz activity. These repetitive HFOs reflected population spikes with hypersynchronous multi-unit firing, and were only found in those FPI rats that later developed seizures.…”
Section: Hfos In Models Of Epilepsymentioning
confidence: 99%
“…72; 73 In FPI rats, a microelectrode and cortical screws recorded pathological HFOs (100–600 Hz) in cortical areas adjacent to or within the injury core during the first two weeks following injury. 74 Moreover, pathological HFOs have been reported to occur in almost 60% of FPI rats, but in none of the control rats. In FPI rats that had completed long-term monitoring, pathological HFOs were found in only those rats that later developed post-traumatic seizures, but were not observed in rats that did not develop late seizures.…”
Section: Hfos In Models Of Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Reports from the animal literature have suggested 3 additional changes in routine noninvasive EEG that appear to correlate with epileptogenesis or ictogenesis. In the fluid percussion TBI rat model, arcuate‐shaped discharges can be recorded with skull screws adjacent to the injury, which appear to predict which animals will eventually develop PTE . Microelectrode recordings demonstrate that these arcuate events reflect the presence of pHFOs (Fig.…”
Section: Other Potential Eeg Biomarkersmentioning
confidence: 87%
“…In the latter study, whereas interictal spikes increase postictally when seizure threshold is high, pHFOs do not increase, but they do increase after medication reduction when seizure threshold is reduced, demonstrating that pHFOs more reliably indicate the degree of epileptogenicity than interictal spikes . Animal studies have demonstrated that pHFOs occur early after 2 epileptogenic insults, intrahippocampal kainic acid injection and fluid percussion TBI, and reliably predict animals that will go on to have spontaneous seizures. pHFOs have yet to be confirmed as reliable biomarkers of epileptogenesis in patients.…”
Section: Phfosmentioning
confidence: 99%